Youtube For Developing Technological Skill - Muhammad Kristiawan; I Gusti Agung Ayu Mas Oka; Een Yayah Haenilah; Wachidi Wachidi; Ediansyah Ediansyah; Iwan Aprianto; Ahmad Zulinto; David D Perrodin; Hendri Budi Utama (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
There are many teachers do not have skill on operating computer specially to make materials interesting for their students. This study was to improve the technological skills of students, particularly those who teach online. In this study, we attempted to determine how students may utilize YouTube as a medium to strengthen their technological skills. This study was carried out by us with the help of students who took the Education Management Course as the subject of study. The data collection technique used in this study was observation sheets, which were then used to answer the formulation of how the student responses related to the video-making project in the Education Management Course uploaded on YouTube; then, to answer the formulation of how the student’s activities on Education Management, we asked students to complete their video projects and upload them on YouTube; and to answer the formulation of whether the use of YouTube can develop technological skills of students, observation sheets was used. This study concludes that respondents are able to edit and upload video about Education Management on YouTube.